Предмет: Алгебра,
автор: nAsTyAsUpErYeS
(3m-1)(m+2)-(m+3)(2m-1)
при m=0.5
(x-2)(3x+1)+(3x-1)(x+2)
При x= -0.5
Ответы
Автор ответа:
1
(3m-1)(m+2)-(m+3)(2m-1) = 3m²+6m-m-2-2m²+m-6m+3= m²+1
m = 0.5
(0.5)² + 1 = 0.25 + 1 = 1.25
(x-2)(3x+1)+(3x-1)(x+2) = 3x²-6x+x-2+3x²+6x-x-2 = 6x²-4
x= -0.5
6*(-0.5)² - 4 = 6 * 0.25 - 4 = 1.5 - 4 = -2.5
Похожие вопросы
Предмет: Физика,
автор: jonickgamse
Предмет: Геометрия,
автор: ilya1274
Предмет: Алгебра,
автор: lizashamarovaliza
Предмет: Математика,
автор: галя1510
Предмет: Математика,
автор: 90010